Occupational Diseases Workers’ Protection as a Important Aspect on OSH Program - Sudi Astono; Ma'ruf Akbar; Moch. Asmawi (IJHCM (International Journal of Human Capital Management), 2019)
Abstract The Aim of this study are to answer the question: "Why is the attention to protection of workers against the occupational disease (OD) is less than to protection against the occupational accident/injury (OA/OI)?" The method used in this study consisted of two processes, namely collecting documents and information, and conduct a analysis of documents and information related to the aspects of the OD in the Occupational and Safety (OSH) program. Information was also obtained through the interviews, discussions, and attending OSH program activities or meetings which carried out by the MOM and also by keys stakeholders.The results of the study that have been conducted show that the number of OD cases that handled and received of work compensation is less than the OI cases.